2015
DOI: 10.1111/eth.12424
|View full text |Cite
|
Sign up to set email alerts
|

The Oxidative Cost of Acoustic Signals: Examining Steroid Versus Aerobic Activity Hypotheses in a Wild Bird

Abstract: Vertebrate vocalizations are widespread secondary sexual signals used for mate attraction and territory defence, and variation in signal quality is often condition dependent and impacts reproductive outcomes. Although vocal signal performance is known to reflect various aspects of male quality, few studies have examined the underlying mechanisms mediating its costs and hence its honesty. Using a population of Arctic-breeding snow buntings (Plectrophenax nivalis), we compared the 'Oxidation Handicap Hypothesis'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 62 publications
2
10
0
Order By: Relevance
“…This correlative relationship suggests that oxidative costs arising from song prevent low-quality males from singing at a higher rate. To the best of our knowledge, this is the only study thus far suggesting that song activity is costly in terms of oxidative stress (Baldo et al, 2015). However, from such a correlative approach it is impossible to discern whether the effect was directly caused by singing activity or indirectly induced by other trade-offs that individuals have to face when singing in the wild.…”
Section: Oxidative Status and Song Activitymentioning
confidence: 93%
See 4 more Smart Citations
“…This correlative relationship suggests that oxidative costs arising from song prevent low-quality males from singing at a higher rate. To the best of our knowledge, this is the only study thus far suggesting that song activity is costly in terms of oxidative stress (Baldo et al, 2015). However, from such a correlative approach it is impossible to discern whether the effect was directly caused by singing activity or indirectly induced by other trade-offs that individuals have to face when singing in the wild.…”
Section: Oxidative Status and Song Activitymentioning
confidence: 93%
“…In the last decades several studies have investigated the role of the redox state in mediating the expression of visual secondary sexual traits (Alonso-Alvarez et al, 2007;McGraw, 2008;Svensson and Wong, 2011;Garratt and Brooks, 2012;Hill and Johnson, 2012;Simons et al, 2012), but until now only few of them focused on birdsong (Van Hout et al, 2011;Casagrande et al, 2014Casagrande et al, , 2015Baldo et al, 2015;Costantini et al, 2015; Table 1). Studies carried out in captive male European starlings (Sturnus vulgaris) to investigate whether song activity can honestly convey information about the redox state, reported that the administration of dietary lutein through the diet was associated with an increase in song rate (Van Hout et al, 2011;Casagrande et al, 2014Casagrande et al, , 2015.…”
Section: Oxidative Status and Song Activitymentioning
confidence: 99%
See 3 more Smart Citations